The citizen and the state: evidence from field experiments - Chaudhry, Zain (2023)
A systematic lack of state capacity is one of the biggest challenges faced by developing countries. One reason for low state capacity is that citizen-state interaction can be stuck in a bad cycle of low trust and low capacity. Such a stark citizen-state trust deficit can lead to poverty and instability. This necessitates an understanding of how the state functions and how policymakers can improve state functioning. This would strengthen citizens' trust in the state. To understand what policies improve public-service delivery and improve citizens' interaction with the state, we need careful evaluation of policy instruments to help us understand the relationship between policy and outcome. This contributes to good public governance by helping governments improve public policies that can lead to higher quality of public service provision and thus higher economic development. In light of this, this thesis aims to illuminate different aspects of state capacity and citizen-state interactions. How can we help improve state functioning? How can the state improve cooperation among citizens and with itself? In all chapters, I collect primary data in Pakistan which allows me to study these phenomena.
Keywords: Hochschulschrift